MENTAL ACTS OF MATHEMATICALLY GIFTED STUDENTS WHEN SOLVING FRACTIONS PROBLEMS - Ikhwanudin, Trisno (RANGE: Jurnal Pendidikan Matematika, 2021)
In the classroom, we will find various types of students with their special learning needs. One group of learners who have different learning needs are gifted students. The paper will focus on the study of mathematically gifted students. This research aims to obtain a description of the mathematically gifted students’ mental acts when solving fractions problems. The respondents were two students of the 7th graders in junior high school, in the West Java Province, Indonesia. The research approach was qualitative. The data were collected through paper and pencil measure, observation, and interview. The data were analyzed by grounded theory with coding and constant comparison. The results show four types of mental acts, those are interpreting, explaining, problem-solving, and inferring. The results of this study can be made as one of didactic anticipation when teachers teach the concept of fractions to the mathematically gifted student. These findings are significant to be considered by the teacher when teaching the mathematically gifted student. Teachers should anticipate how students think when they teach gifted students. So that teachers and students can achieve optimal learning outcomes.